GEOSTATIONER SATELLITE DATA FOR RAINFALL ESTIMATION - Aljabaro , Riko
Recently update rainfall information is highly needed. In Indonesia, precipitation data are received from rain gauge that locate in climatology stations. However, these data cannot represent unique topography of Indonesia. To overcome these problems, using satellite data is an alternative solution. One method of rainfall estimation that uses geostasioner satellite data which call Convective Stratiform Technique (CST) is used in this research. This CST method uses top cloud temperature as input data and convert it to rainfall. This process is done by signing minimum temperature in one place and its surrounding to clasify the cloud type and then calculate the estimation value of the rainfall. The result of rainfall estimation using CST method for Sumatera and Java Island cannot indicate high precipitation result. The total hourly precipitation result is less than 15 mm. In December 2006, the correlation between average estimation and observation show better result, which is 0.16 than the correlation in a point, which is 0.04. Also in December 2006, daily correlation also show better result than hourly correlation, which is 0.23. The weakness of CST method for a high precipitation value can be modified by adding growth factor value. This modification give better correlation, which is 0,63. According to this result, the modification of CST method by adding growth factor can be used to estimate daily rainfall.